NURSING CONTRIBUTIONS TO CARE MANAGEMENT IN PRIMARY HEALTH CARE: A LITERATURE REVIEW - Sesnik, Heitor Hortensi; Moura, Débora Regina de Oliveira; Delmondes, Nataly Cristine dos Santos Oliveira; de Almeida, Maria Julia Elias; Bernardo, Pedro Henrique Paiva; Caniato, Maria Heloiza Bezerra; Sala, Caroline; Palmieri, Isadora Gabriella Silva; Menon, Giulia Meneses; de Souza, Letícia Baio; Magnabosco, Gabriela Tavares (Seven Editora, 2025)
Introduction: Primary Health Care (PHC), mainly structured through the Family Health Strategy (FHS), is the main entry point to the Unified Health System (SUS). In this context, nursing plays a central role both in care delivery and in care management. Given the structural and organizational challenges, this study aimed to analyze the contributions of nursing in care management within PHC.Methodology: This is a descriptive study based on a literature review. Articles published in the last five years, in Portuguese, English, or Spanish, that addressed nursing management in PHC were included. The search was conducted in the Virtual Health Library (VHL), using the descriptors “Health Management,” “Primary Health Care,” and “Nursing,” combined with the Boolean operator AND. After applying inclusion and exclusion criteria, nine studies were analyzed.Results and Discussion: The studies indicate that nurses perform both care and managerial functions, playing a leading role in organizing services and leading teams. The main challenges include: work overload, insufficient management training, shortage of human and technological resources, and institutional barriers. Despite this, nursing demonstrates problem-solving capacity by using local strategies, accessible technologies, and active participation in decision-making.Conclusion: Nursing plays a strategic role in PHC management, although it faces obstacles that affect the quality of care. Investing in management training, valuing professionals, and clearly defining their responsibilities are fundamental actions to strengthen PHC and SUS.DOI: https://doi.org/10.56238/sevened2025.029-108